Flexural Tensile Strength of Asphalt Composites with Calcined Clay under Four-Point Bending - Spínola, Juliano Rodrigues; da Silva, Antônio Cleiton Lopes; Pereir, Alex Gomes; da Frota, Consuelo Alves (American Scientific Research Journal for Engineering, Technology, and Sciences, 2019)
Replacing natural aggregates for employment in pavement applications has been exhaustively proposed in order to reduce the unsustainable consumption of these materials. An option widely studied in the Amazon Region is the Sintered Calcined Clay Aggregate (SCCA), a promising alternative to the historical scarcity of rocky material, given the region geology, primarily for the strong occurrence of clays. The aim of this research is to study the use of calcined clay aggregates to create an alternative mixture for asphalt coating of urban paved roads. The influence of temperature variation on the mechanical behavior of SCCA asphalt concrete was also evaluated in order to simulate high-temperature zones. Four-point bending tests were performed on prismatic specimens compacted in controlled conditions with the aim to determine the Flexural Tensile Strength. Superpave method was used for the design of asphalt mixes. The test results from this study indicated that the FTS increases with frequency and decreases with temperature. On the other hand, increasing temperature promotes a tendency of stabilization of the FTS, in which the saturation of the asphalt binder can be observed, due to its viscoelastic nature.